Tindak Tutur Berbahasa Inggris Petugas Kantor Depan pada Hotel Melati di Kawasan Wisata Ubud, Bali - I Ketut Murdana (LACULTOUR: Journal of Language and Cultural Tourism, 2022)
The research entitled “The Use of Speech acts types on the English Speech of the Front Office Staff at Some Small Scaled Hotel in Ubud Tourist Resort Gianyar Regency Bali” discusses one research problem which is the use of speech acts types on English speech of the Front Office staff in communicating with the hotel guests. The theory applied to analyse data is Pragmatic Theory that is speech acts types theory proposed by Searle (1969) and Wijana (2015). The research findings on the use of speech acts types on English speech of the Front Office staff at some small scaled hotel in Ubud Tourist Resort Gianyar Bali is that all those 10 speech acts proposed by Searle (1969) and Wijana (2015) which are: (1) locutionary acts, (2) ilocutionary acts, (3) perlocutionary acts, (4) assertives acts, (5) reformatives acts, (6) verdivtives acts, (7) expressives acts, (8) directives acts, (9) commisives acts, (10) fatice acts have all already been used in English speech of the informants of the Front Office staff eventhough the use are not yet as on the whole of every speech event occurred.